PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP BIAYA EKUITAS DAN BIAYA UTANG (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI pada Tahun 2010-2012) - Dwi Ricky Nugroho; Wahyu Meiranto (Diponegoro Journal of Accounting, 2014)
This research aims to determine the impact of good corporate governance to cost of equity and cost of debt. The proxy of good corporate governance is family ownership, managerial ownership, institutional ownership, frequency of audit committees meeting, audit quality, and independent commissioner. While the dependent variable used in this research is cost of equity was assessed by using the measurement model Ohlson and cost of debt which is rated by using the measurement of cost of debt (COD). In addition, this research also added three control variables are leverage, firm performance, and firm size. This study used secondary data with entire population of manufacturing companies listed in the Indonesia Stock Exchange (BEI) in 2010-2012. The method used to determine the sample using purposive sampling. The analytical method used is multiple linear regression, regression testing prior to first tested the classical assumptions.The result of this research showed that institutional ownership and frequency of audit committees meeting positive significant with cost of equity. Other result noted that audit quality is negatively significant with cost of equity. While family ownership, managerial ownership, and independent commissioner did not significantly affect with cost of equity. And the result of this research also showed that audit quality is negatively significant with cost of debt. Other result noted that independent commissioner positive significant with cost of debt. While family ownership, managerial ownership, institutional ownership, and frequency of audit committees meeting did not significantly affect with cost of debt. Overall it can be concluded from these results that the good corporate governance affect cost of equity and cost of debt.